Expert or charlatan? the rise and rise of management consulting - Louth, John (KW Publishers, 2014)
This book seeks to make good that deficiency in our perception of the profession. Leaning on his deep and wide-ranging experience, Dr John Louth seeks to lift the lid on the management consulting profession in a critically reflective and accessible manner. With vignettes and examples drawn from his own experience and practice, he dissects the rational explanations usually provided by practitioners. He calls for restraint and self-awareness from both client and consultant, and advocates the reform of.15 a profession that seems increasingly powerful and unregulated